33. Ore Deposits in the Central San Juan Mountains, Colorado - Thomas A. Steven (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Most mineralized areas in the central San Juan Mountains, Colorado, are associated with the youngest subsidence structures in a large volcanic cauldron complex that formed concurrently with eruption of the surrounding ash-flow field. Two local types have been recognized: (1) fissure-vein deposits along faults characterized by relatively late movement, and (2) hydrothermally altered and mineralized areas associated with postsubsidence Fisher Quartz Latite centers. The first type has provided most production in the past; the potential of the second type has yet to be adequately tested.